Optimalisasi pengembangan geowisata Gua Bokimoruru sebagai Taman Bumi Studi Desa Sagea Kecamatan Weda Utara Kabupaten Halmahera Tengah - Hakim Asura; Batara Surya; S. Kamran Aksa (Fakultas Teknik Universitas Bosowa, 2021)
The purpose of this study was to determine the factors of the Bokimoruru Cave tourist attraction that had not developed optimally, namely with the potential for tourist attraction there, it turned out that the accessibility factor and information media had a significant effect so that the Bokimoruru Cave tourist attraction was tested using SWOT analysis tools and Linear regression. Factors that have a significant direct effect on Geotourism Bokimoruru Cave from the results of linear regression analysis, there are three 3 tourist attraction stimulants X1, Tourism Facilities X2, X3 Infrastructure the results are rejected meaning that it has a significant effect on Bokimoru Cave on tourist attractions, tourist facilities and resources While the factors that have an indirect and insignificant effect on Geotourism of Bokimoruru Cave from the results of linear regression analysis, there are two, namely the stimulant of information and publication factors X4, X5 accessibility, then the results are accepted, meaning that it does not significantly affect Bokimoru Cave on information and publication media. not expected.